THE PROBLEMS OF USING MEDIA CONTENTS IN TEACHING - Turayeva Nigora Nurdinovna (Western European Studies, 2024)
This article discusses the problems of using media content in teaching. It is shown that the use of e-learning in the educational process naturally leads to an increase in the level of media competence of the individual, both the teacher himself, who uses new educational technologies, and the student, who uses new information technologies of education. A number of problems associated with the formation of media competence of students when using elearning systems and technologies in the educational process of an educational institution of higher education are considered. The object of the study is the process of learning using elearning technologies, aimed at forming the media competence of the individual.
Keywords: media education; media competence of the individual; media content